PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) PADA MATA PELAJARAN PENERAPAN SISTEM RADIO DAN TELEVISI KELAS XI DI SMK NEGERI 39 JAKARTA - Lutfatunnisa; Moch. Sukardjo; Arum Setyowati (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2025)
The use of technology in creating learning media can help teachers convey information to students, one of which is using Augmented Reality. Augmented Reality is a technology that combines the real world with the virtual world. Augmented Reality learning media wa developed based on the problems that occurred in the teaching and learning process of the subject of application of radio and television systems for class XI at SMK Negeri 39 Jakarta. The purpose of this study was to develop and determine the feasibility of Augmented Reality based learning media in the subject of application of radio and television sysems for class XI at SMK Negeri 39 Jakarta. The method used in this study is the research and development (R&D) method using 6 stages, namely potential and problems, data collection, product design, design validation, design revision, and product testing. Augmented Reality-based learning media using Assmblr Edu wasvalidated by instructional design experts, media experts, and material experts. The results of the feasibility test by instructional design experts were 72,76%, media experts were 84%, and material exprts were 98,8. So that the Augmented Reality-based learning media as a whole was suitable for use by students in the learning activities of the Applcation of Radio and Television System subject for class XI at SMK Negeri 39 Jakarta. Keywords : Learning Media, Augmented Reality, Assemblr Edu